EVALUATION OF (SELF-)DEVELOPMENT OF INTERCULTURALITY EXPERIENCES IN INFORMAL LEARNING ENVIRONMENTS - Bilbokaitė-Skiauterienė, Ieva; Bilbokaitė, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Political, economic, social and cultural changes of the country influence the change of the educational content. Striving to develop dynamic modern Lithuanian’s and person’s modern nationality, the educational content should relate to “pupils’ experiences and sociocultural needs. The article presents that the development of interculturality of pupils is one of the approaches when striving to understand cultural diversity of the present-day world.The results of previous research (Bilbokaitė, 2017, 2016) have revealed the lack of programmes, clear guidelines for intercultural education in the context of the different learning environments. The article describes importance of informal education, that arises from the learner’s involvement in activities that are not undertaken with a learning purpose in mind.The research aim is to reveal pupil’s (of the 10th-12th Forms) opinion about the (self-)development of interculturality in informal learning environments. Quantitative research was used (sample of 727 Lithuanian comprehensive school pupils) to investigate practical application of development of interculturality in educational environment from pupil’s perspective. The research results analysed employing content analysis reveal the importance of learning from the experience as a fundamental and natural means in different environments - home, social networks, school, city, streets. Safe personal environment creates the opportunity to be self, to learn about values, variety of cultures, tolerance, acceptance of others. Pupils’ opinions concerning the lack of possibilities for development of interculturality in school (during formal education) are presented.